Layer structure formation in Hg₁₋xCdxTe films after high-frequency sonication - Savkina, R.K.; Sizov, F.F.; Smirnov, A.B.; Tetyorkin, V.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2006)
Electrophysical parameters of Hg₁₋xCdxTe thin films grown by liquid-phase epitaxy and molecular-beam epitaxy were investigated before and after the high-frequency sonication ( fUS = 7.5 MHz, WUS ~ 10⁴ W/m²). It was determined that parameters of MBE-grown Hg₁₋xCdxTe thin films are stable to ultrasound effect, while for thin films grown by LPE the sonically stimulated change of the conductivity type was observed. The best agreement between experiment and calculation was obtained in the frame of the assumption about forming of the thin layer with another conductivity type. The possible nature of the observed effect was analyzed.